2003
DOI: 10.1080/14034940210164902
|View full text |Cite
|
Sign up to set email alerts
|

Unemployment - an important predictor for future smoking: a 14-year follow-up study of school leavers

Abstract: It is possible already at school to identify risk groups for future smoking and high alcohol consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
3
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 8 publications
3
20
3
2
Order By: Relevance
“…Nossos resultados corroboram os estudos que mostram o desemprego positivamente associado ao tabagismo 23,24 , associação que se torna ainda mais intensa quanto maior a duração de desemprego 25 . Ao estudar trajetórias no mercado de trabalho (emprego estável até desemprego de longa duração) e mudanças na situação de fumante/não fumante ao longo de cinco anos, Virtanem et al 26 verificaram que os homens que se encontravam desempregados na linha de base e no seguimento fumavam mais cigarros/dia do que os que trabalhavam.…”
Section: Discussionunclassified
“…Nossos resultados corroboram os estudos que mostram o desemprego positivamente associado ao tabagismo 23,24 , associação que se torna ainda mais intensa quanto maior a duração de desemprego 25 . Ao estudar trajetórias no mercado de trabalho (emprego estável até desemprego de longa duração) e mudanças na situação de fumante/não fumante ao longo de cinco anos, Virtanem et al 26 verificaram que os homens que se encontravam desempregados na linha de base e no seguimento fumavam mais cigarros/dia do que os que trabalhavam.…”
Section: Discussionunclassified
“…Contradictory results have also been found for the likelihood of using more alcohol and tobacco after becoming unemployed. While some studies have uncovered a relationship between unemployment and increased alcohol consumption and smoking in unemployed men only (Reine et al 2013), a Swedish study found that this association was attenuated in women after controlling for having children (Janlert and Hammarstrom 1992;De Vogli and Santinello 2005;Bolton and Rodriguez 2009), and yet another study found that young women smoked more after becoming unemployed (Hammarström and Janlert 2003). An international comparison has shown that gender differences in the effects of unemployment on health differ in Ireland and Sweden.…”
Section: Employmentmentioning
confidence: 99%
“…This association has been interpreted as a selection mechanism from smoking into unemployment (Bartley 1994;Bartley 1996;Elkeles and Seifert 1993;Jusot et al 2008) as well as a causal effect of unemployment on smoking behaviour (Bartley 1994;Bartley 1996;Elkeles and Seifert 1993;Hammarstrom and Janlert 2003). In contrast to this, what we term here the "common cause hypothesis" assumes a third variable, i.e.…”
Section: Introductionmentioning
confidence: 82%
“…At the same time, there is evidence that unemployment increases smoking probability for Sweden (Hammarstrom and Janlert 2003), with mixed evidence from the U.S. (Bolton and Rodriguez 2009;Falba et al 2005;Gallo et al 2005;Ryan, Zwerling and Jones 1996), Britain (Montgomery et al 1998;Morris, Cook and Shaper 1992), and Germany (Marcus 2012;Schunck and Rogge 2012) and no evidence for such a relation in Finland (Virtanen et al 2008) and Denmark (Osler 1995 Proponents of the causation hypothesis (see figure 1) have predominantly made reference to stress theory to account for health changes after job loss (Pearlin 1989;Thoits 1995;Umberson, Lui and Reczek 2008). They assume that unemployment increases psychological distress and individuals, in order to reduce this distress, draw on potentially health-damaging behaviours (De Vogli and Santinello 2005;Siegrist and Rodel 2006).…”
Section: Figure 1: Possible Mechanisms Relating Unemployment and Smokingmentioning
confidence: 93%